The boundaries of ancient trade: kings, commoners, and the Aksumite salt trade of Ethiopia - Solomon-Woldekiros, Helina, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
An integrated ethnoarchaeological and archaeological investigation of the Afar salt route in and around the early Aksumite State in the Horn of Africa that explores the relationships between the fringes of the Aksumite polity and core power structures.--Provided by publisher.
Introduction. Rethinking trade and power in Archaeology -- Hierarchies, heterarchies, peer networks, trade, and ethnoarchaeology of caravans: interpretive frameworks for the study of the salt trade -- Aksumite political economy -- The physical and social landscapes of the Afar salt trade network -- The ethnoarchaeology of salt production and trade -- The archaeology of the salt trade: settlement patterns and features -- Heterarchies, hierarchies, and peer networks: Afar salt caravan trade and Aksumite political economy.
Keywords: Salt industry and trade -- Aksum (Kingdom); Salt industry and trade -- Ethiopia -- History; Trade routes -- Africa; Afar (African people) -- Antiquities; Ethiopia -- Antiquities; Aksum (Kingdom) -- Antiquities